If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + k = 9 Solving 6 + k = 9 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + k = 9 + -6 Combine like terms: 6 + -6 = 0 0 + k = 9 + -6 k = 9 + -6 Combine like terms: 9 + -6 = 3 k = 3 Simplifying k = 3
| 13y+x+7y= | | 5a+a+2a+9-6a+33= | | 2x^2+4x=400 | | x/-4=-90 | | 9p-6p=-8+11 | | A+30=2A+30 | | x^3+25x+144=0 | | b/5=30 | | 2/5w=8 | | 4+x/7=10 | | -(3y+3)-(-2y-5)=-4 | | x+-4=-90 | | 3y^2+16y=-5 | | 245=-y+183 | | -9[-2]+4f=7f-3 | | 112=120-4x | | 92/4 | | tanx*sinx+sinx=0 | | 9+(-11)=4x-3x+5 | | 5n^2-17=58 | | 13y-18=(-5)y+36 | | .75x+2-6=.5x-12 | | 3x^2-18=-18 | | 133/7 | | 2=182-x | | 6u-9u=6[-2]+u | | x*7=-350 | | 2+10x=x-7[-8] | | 3(x-3)=5(1.5m+x) | | (5x-3)(5x-3)=49x^2 | | 5xn=2.28 | | 3(x-3)=5(1.5m+3)+3.5m-1 |